Development and Validation of Contemporary Qur'anic Teaching Materials: An ADDIE Model Approach to Enhancing Student Engagement and Learning Outcomes - Sada, Heru Juabdin; Fadila, Abi; Handayani, Lusi; Yunian Putra, Rizki Wahyu (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aimed to develop and evaluate teaching materials for the Contemporary Qur'anic Teaching Methods course, using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The material was designed to address the lack of a primary reference resource for the course, aligning with the curriculum and competencies required for effective learning. Subject matter and media experts validated the content, confirming its academic rigor and visual appeal. The teaching material was trialed with students in both small-scale and large-scale settings, with positive feedback indicating high engagement and effectiveness in supporting student learning. The study found that the material successfully integrated contemporary pedagogical approaches with traditional Qur'anic teaching, enhancing both academic understanding and student engagement. Despite its success, the study highlighted areas for improvement, such as the incorporation of more multimedia elements and a larger, more diverse sample for future trials. The findings suggest that modernizing Qur'anic education through innovative teaching materials can significantly improve learning outcomes, offering a model for the development of similar resources in Islamic studies. This research contributes to the growing body of work aimed at integrating contemporary teaching methods into religious education and offers valuable insights for educators seeking to enhance their instructional practices in Qur'anic studies.